Antimicrobial activity of Chlorhexidine, Peracetic acid and Sodium hypochlorite/etidronate irrigant solutions against Enterococcus faecalis biofilms. (8th January 2015) - Arias‐Moliz, M. T.; Ordinola‐Zapata, R.; Baca, P.; Ruiz‐Linares, M.; García García, E.; Hungaro Duarte, M. A.; Monteiro Bramante, C.; Ferrer‐Luque, C. M.
Abstract Aim To evaluate the antimicrobial effect of 2.5% sodium hypochlorite alone (NaOCl) and associated with 9% HEBP (NaOCl/HEBP), 2% peracetic acid (PAA) and 2% chlorhexidine (CHX), on the viability of Enterococcus faecalis biofilms attached to dentine. Methodology Biofilms of E. faecalis were grown on the surface of dentine blocks for 5 days and then exposed to the irrigating solutions for 3 min. Distilled water was used as the control. The total biovolume and the percentage of dead cells of the infected dentine were measured by means of confocal microscopy and the live/dead technique. Nonparametric tests were used to determine statistical differences (P < 0.05). Results NaOCl and the NaOCl/HEBP mixture were associated with a significantly greater percentage of dead cells, followed by PAA (P < 0.05). No significant antimicrobial effect of CHX was observed in comparison with the control group. Total biovolume decreased significantly in NaOCl, NaOCl/HEBP and PAA solutions in comparison with the CHX and control groups. Conclusions NaOCl alone or associated with HEBP were the most effective irrigant solutions in dissolving and killing E. faecalis biofilms.